Social Return on Investment (SROI) Analysis on Social Project in Hegar Manah Village - Goenadhi, Felix (Lentera Ilmu Madani, 2025)
This report presents a Social Return on Investment (SROI) analysis for a community streetlight installation project in Hegar Manah Village, a location with a historically high rate of motorcycle theft and associated social harms. The core objective of the initiative is to enhance public safety and reduce criminal activity by improving road illumination in a known hotspot for crime. The SROI methodology—a framework that quantifies and monetizes social, economic, and emotional outcomes—is employed to provide a comprehensive evaluation of the project's value beyond basic financial metrics. Key calculation parameters include an annual prevention of 4.5 robbery cases, each with an average social cost of Rp 57,000,000, resulting in a total avoided cost of Rp 256,500,000 per year. After applying adjustment factors for deadweight and attribution, the net annual social value is Rp184,680,000. With an initial project cost of only Rp3,400,000, the resulting SROI is 54.3: every Rp1 invested generates approximately Rp54.30 in social value. Projecting the impact over five years, the SROI rises to 271.6, underscoring the high effectiveness and scalability of this intervention. Complementary literature and empirical studies corroborate the significant crime-reducing effects of street lighting, supporting the robust outcomes observed in this case study. The findings demonstrate that targeted infrastructure projects can generate substantial social and economic benefits, making a strong case for community-driven safety initiatives